Social Problems Become a Challenge for Strengthening Community Character through the Implementation of Village Critical Thinking - Luh Kinga Li (Akademi Sertifikasi Profesi Internasional, 2024)
Social problems that occur among young people in the modern era, especially in the midst of the rapid development of globalization, certainly have a big impact on the level of morality and character formation of the nation's young generation. This is evidenced by how many social problems are found in the midst of society from villages to cities, from remote to all-around. Many of the causes are due to the mindset and character education that are still minimal in the community. One of these phenomena was found in the Village Area. The way to overcome the problems that occur is by providing assistance through socialization to the younger generation through community institutions and activities. Data was obtained from observations and interviews with competent parties, socialization involving students from several institutions and village youth who are members of existing community groups.